1995
DOI: 10.3109/00016349509009947
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacterial vaginosis in wet mount, Papanicolaou stained vaginal smears and in Gram stained smears

Abstract: In a prospective study of 107 women, bacterial vaginosis was clinically diagnosed in 34 women. Compared with clinical diagnosis of bacterial vaginosis, detection of clue cells in Papanicolaou stained vaginal smears showed a sensitivity of 88.2%, a specificity of 98.6%, a positive predictive value of 96.8% and a negative predictive value of 94.7%. The corresponding values for detection of bacterial vaginosis in Gram stained smears compared with the clinical diagnosis were 100%, 97.3%, 94.4% and 100%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…The positive predictive values were determined as 86% for Pap smear and 88% for Gram stain. The aforementioned rates are similar to rates determined by PlatzChristensen and colleagues 9 . But the specificity rate of our study is smaller than the that determined by Platz-Christensen and colleagues.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The positive predictive values were determined as 86% for Pap smear and 88% for Gram stain. The aforementioned rates are similar to rates determined by PlatzChristensen and colleagues 9 . But the specificity rate of our study is smaller than the that determined by Platz-Christensen and colleagues.…”
Section: Resultssupporting
confidence: 74%
“…These rates were 100%, 97%, and 94% respectively for the Gram stain method 9 . In our study, the observed sensitivity and specificity were 93% and 94% respectively for Pap smear, and 97% and 94% respectively for Gram stain.…”
Section: Resultsmentioning
confidence: 95%
“…Interestingly, we have observed that in Pacoti, for many women, the main reason to have a Pap smear done was the presence of gynaecological complaints, usually an abnormal vaginal discharge, rather than the opportunity to participate at a cancer screening programme free of charge (F. A. Oliveira, unpublished observation). The Pap smear, although not a recommended method for the diagnosis of vaginal infections, has a sensitivity of 60% for the detection of Trichomonas vaginalis infection and 88% for bacterial vaginosis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that this infection could lead to diverse upper genital tract infections. According to the literature data, women with BV have an increased relative risk of post partum endometritis, post cesarean wound infection, premature rupture of membranes, premature labor, intra-amniotic infection and pelvic inflammatory disease (PID) (8,9,10,11,12). In the literature, the relation between several infections such as actinomycosis, trichomoniasis and IUCD was reported (13,14).…”
Section: Introductionmentioning
confidence: 99%